If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3a + 7(5a + 7b) + -10(3 + 5b) = 14ab + 50(3 + 4) 3a + (5a * 7 + 7b * 7) + -10(3 + 5b) = 14ab + 50(3 + 4) 3a + (35a + 49b) + -10(3 + 5b) = 14ab + 50(3 + 4) 3a + 35a + 49b + (3 * -10 + 5b * -10) = 14ab + 50(3 + 4) 3a + 35a + 49b + (-30 + -50b) = 14ab + 50(3 + 4) Reorder the terms: -30 + 3a + 35a + 49b + -50b = 14ab + 50(3 + 4) Combine like terms: 3a + 35a = 38a -30 + 38a + 49b + -50b = 14ab + 50(3 + 4) Combine like terms: 49b + -50b = -1b -30 + 38a + -1b = 14ab + 50(3 + 4) Combine like terms: 3 + 4 = 7 -30 + 38a + -1b = 14ab + 50(7) Multiply 50 * 7 -30 + 38a + -1b = 14ab + 350 Reorder the terms: -30 + 38a + -1b = 350 + 14ab Solving -30 + 38a + -1b = 350 + 14ab Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-14ab' to each side of the equation. -30 + 38a + -14ab + -1b = 350 + 14ab + -14ab Combine like terms: 14ab + -14ab = 0 -30 + 38a + -14ab + -1b = 350 + 0 -30 + 38a + -14ab + -1b = 350 Add '30' to each side of the equation. -30 + 38a + -14ab + 30 + -1b = 350 + 30 Reorder the terms: -30 + 30 + 38a + -14ab + -1b = 350 + 30 Combine like terms: -30 + 30 = 0 0 + 38a + -14ab + -1b = 350 + 30 38a + -14ab + -1b = 350 + 30 Combine like terms: 350 + 30 = 380 38a + -14ab + -1b = 380 Add 'b' to each side of the equation. 38a + -14ab + -1b + b = 380 + b Combine like terms: -1b + b = 0 38a + -14ab + 0 = 380 + b 38a + -14ab = 380 + b Reorder the terms: -380 + 38a + -14ab + -1b = 380 + b + -380 + -1b Reorder the terms: -380 + 38a + -14ab + -1b = 380 + -380 + b + -1b Combine like terms: 380 + -380 = 0 -380 + 38a + -14ab + -1b = 0 + b + -1b -380 + 38a + -14ab + -1b = b + -1b Combine like terms: b + -1b = 0 -380 + 38a + -14ab + -1b = 0 The solution to this equation could not be determined.
| 2[3x+2(x-2)]+19=(3x+1)*2 | | 8x+3-(7+9x)=-8 | | 2(3c+2d)-2(5c-3d)= | | -(3y-1)-3y+7=2 | | 2x^3-11x^2-x+5=0 | | 3(x+2)=5(3x-2) | | y=x^4-2x^3-3x^2 | | y=80x-5x^2+2 | | 24x+x^2=-1 | | ln(x/(x-9)) | | 3x+ky=25 | | (2x+4)2=25 | | (8x-5)+1=9(x+5) | | 31x^2+5=0 | | x+-7=-6 | | [8x-5]+1=9[x+5] | | ae-yd=y*y | | (-3x-6)(x-1)=0 | | a+0+y+d+e=d(0) | | -5x(5x-5)= | | x+(-7)=-15 | | 5(x-3)-2(x+4)=(x-3)+4(x-1) | | a^4-a^2+5=0 | | 3(x+8)=38-4x | | cos3y=1/2 | | 3x^2+41x-170=0 | | X-(2x+5)=-2(x+4)+19 | | -(2x+5)=2(x+4)+19 | | 60x/120x | | 4(x+4)=2(x+20) | | -8(3y+5)+y=-1 | | 25x+20=5x+40 |